The Idea of German University. A Humboldt Myth? - Sosnowska, Paulina (INSTED: Interdisciplinary Studies in Education & Society, 2012)
This paper is an analysis of the debate concerning higher education that has been taking place among German intellectuals since World War II. The purpose of this research is: firstly ? to trace back the relationship between the presuppositions of the Prussian reform and its historical realization, pointing out social and political contexts of the reshaping of the German higher education system and outlining a map of possible stances in this debate; secondly ? to present the problem of autonomy of German universities from the perspective of this debate and the paradoxical relationship between idea and reality, theory and practice; thirdly ? to relate these analyses to the contemporary conditions of Polish higher education and make an attempt to show this condition from an external, yet close perspective, as the Humboldtian idea and its legacy seems to be.